EXPLORING THE MENTAL HEALTH PROMOTION OF NURSES TO PREOPERATIVE CARDIOVASCULAR DISEASE PATIENTS IN ASTANA: AN EXPLORATORY QUALITATIVE STUDY - Shaldarbek, Alpamys (Nazarbayev University School of Medicine, 2025)
Introduction: This study explores how nurses in Astana, Kazakhstan, promote the mental health of preoperative cardiovascular disease (CVD) patients. Despite advancements in medical care, the psychological needs of CVD patients remain under-addressed, and the role of nurses in mental health promotion is still underexplored. Aim: The research aims to explore how nurses in Astana (Nur-Sultan) promote the mental health of preoperative cardiovascular disease (CVD) patients Methods: This research used an exploratory qualitative method. Data was collected through semi-structured interviews with ten nurses at the UMC Heart Center in Astana, Kazakhstan, specifically from cardiac surgery units. The interviews were conducted from March to April 2025, and the thematic analysis was used to analyze the data. Results: Initially, the data had 96 codes. Then, it was grouped to develop 19 subthemes and further categorized into four major themes. The main themes are “Patient Emotional Support Needs,” “Challenges to Mental Health Promotion,” and “Influencing Factors in Mental Health Promotion.” Conclusion: Nurses play a vital role in supporting the mental health of CVD patients, where communication and presence are the primary bases.
Keywords: Cardiovascular Disease; Mental Health; Exploratory Qualitative; Preoperative; Nurse; type of access: embargo